Perancangan Sistem Informasi Supply Chain Management Pengadaan Barang Perlengkapan Penanganan Covid-19. - Izatun Nihayah; Anna Retno Indrawati; Rubby Harris; Irawan Syaifulloh; Yusuf Amrozi (INFORMAL: Informatics Journal, 2021)
The Supply Chain Management Information System combines several business processes across organizations from the initial organization to the end user. In the procurement of raw materials, the procurement of Covid-19 takes time and causes inventory. With the Supply Chain Management Information System, it is expected to simplify the procurement process and minimize shortages of goods so as to speed up patient handling. This study resulted in the design of an SCM information system that uses the waterfall model software development method which is useful for helping the health industry get the flow of information, goods, and money because the related parties have been integrated with the designed system.